2017
DOI: 10.1080/15476286.2017.1367886
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNAs: Isolation, characterization and their potential role in diseases

Abstract: Circular RNA (circRNA) generated by alternative splicing represents a special class of non-coding RNA molecule. CircRNAs are abundant in the eukaryotic cell cytoplasm and have a characteristic organization, timing of action and disease specificity. In contrast to linear RNA, circRNAs are resistant to RNA exonuclease. Consequently, circRNA escapes normal RNA turnover and this improves circRNA stability. CircRNAs can be degraded by microRNA (miRNA) and this results in linearization of the circRNA, which can then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(80 citation statements)
references
References 75 publications
(107 reference statements)
0
79
0
1
Order By: Relevance
“…Although there is little known about their role in human biological processes, the dysregulation of circRNAs is confirmed in several diseases including cancer. 11,16,17 Up to now, the relation between circular RNAs and ULMs remains unclear. We evaluated the hsa_ circ_0060927 expression level in uterine leiomyoma and adjacent tissue samples by qRT-PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is little known about their role in human biological processes, the dysregulation of circRNAs is confirmed in several diseases including cancer. 11,16,17 Up to now, the relation between circular RNAs and ULMs remains unclear. We evaluated the hsa_ circ_0060927 expression level in uterine leiomyoma and adjacent tissue samples by qRT-PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, multiple MREs are present in ceRNAs and enable direct interactions with miRNAs, thereby preventing binding of these miRNAs to their respective target mRNAs (Figure 1d). The role of ceRNAs in various cellular processes (e.g., cell cycle, apoptosis) is well established, and alteration of their expression contributes to the onset of various pathologies [76][77][78]. One representative and well-studied example of such regulation is provided by the phosphatase and tensin homologue, pseudogene 1 (PTENP1), which can sponge various miRNAs (e.g., miR-21, miR-106b and miR-93) targeting the 3 UTR of the tumor suppressor gene phosphatase and tensin homologue (PTEN) [79,80].…”
Section: Mirna-cerna Interactionsmentioning
confidence: 99%
“…Interestingly, circRNA has been reported that it is also displayed to be abundant in exosomes in serum [16]. Therefore, Li et al suggested that sorting of circRNAs to exosomes was regulated by altering levels of associated miRNA in producer cells [16,22]. In addition, researchers have found that CDR1as including exosomes inhibit miR-7-induced growth in recipient cells [22].…”
Section: Circrnas Can Act As Mirna Spongesmentioning
confidence: 99%
“…Therefore, Li et al suggested that sorting of circRNAs to exosomes was regulated by altering levels of associated miRNA in producer cells [16,22]. In addition, researchers have found that CDR1as including exosomes inhibit miR-7-induced growth in recipient cells [22]. Testesspecific circRNA/circSry [the circular transcript of sex determining region Y (Sry) gene] can also serve as a sponge for miRNA-138 [23].…”
Section: Circrnas Can Act As Mirna Spongesmentioning
confidence: 99%